Experience, Independence, Professional Commitment of Auditors, and Audit Quality (Study at the Sidoarjo Regency Inspectorate) - Rahman, Arief; Fauziah, Dien Ajeng (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to investigate the impact of audit experience, auditor independence, and professional commitment on audit quality at the Sidoarjo Regency Inspectorate. The research methodology employed in this study is descriptive quantitative. The primary data for this research were collected through a questionnaire, and the sampling technique used was saturated sampling. The sample size for this study consisted of 34 auditors or respondents. Prior to analysis, the collected data underwent validity and reliability tests. Multiple linear regression analysis was employed to analyze the data. The hypothesis testing was conducted using SPSS. The findings of this study indicate that both auditor's work experience and professional commitment significantly influence audit quality, whereas auditor independence does not have a significant impact on audit quality.